(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article reviews a survey that included 296 diagnosed cases of acute lymphoblastic leukemia over the age of 12 years. The diagnosis of ALL was made based on bone marrow aspiration, biopsy, flow cytometry, and cytogenetics. In this study, complete remission was observed in 90.9% of cases. The treatment-related mortality rate in our study was 15.3%.